Tunnelling effects on framed buildings - Xu, Jingmin (2020)
The ever-increasing population in the urban environment requires continuous improvement for infrastructure, which often involves tunnel construction. To predict/mitigate tunnelling-induced damage of nearby structures, for instance, surface buildings, engineers need to be able to understand the complex soil-structure interaction mechanisms caused by excavation. Nevertheless, due to the complexity of the problem, simpliﬁcations have to be made; for instance, the frequent use of an equivalent isotropic plate to represent the surface structure, which brings a high level of uncertainty within risk assessments. This dissertation investigates the response of framed buildings with shallow foundations (rafts or separate strip footings) to tunnelling through using data obtained from 44 plane-strain geotechnical centrifuge tests. The research considered 8 elastic framed building models with varying conﬁguration, with tunnelling- and structure-related parameters also varied during tests.